La Bataille de Brunanburh : présentation, traduction et commentaire d’un poème du Xe siècle tiré de la Chronique anglo-saxonne - Alban Gautier (Tabularia)
This paper offers a French translation, along with a commentary, of the Old English poem The Battle of Brunanburh. The battle itself took place in 937 in the North of England: King Æthelstan and his brother and heir Edmund achieved victory over a coalition that included the vikings of Dublin and the Scots under King Constantine II. The poem was composed in honour of the victors and was inserted in five manuscripts (A, B, C, D, G) of the Anglo-Saxon Chronicle.